Implementation of Educational Learning Outcomes Evaluation Islamic Religion is Based on an Independent Curriculum - Achmad Musyafa'; Muhammad Nasir; Fathul Jannah; Sudadi Sudadi (Departement of Mathematics Education, 2023)
The aim of this research is to explain the attributes of the activities included in the process of evaluating or assessing learning outcomes in Islamic religious education sessions, with special emphasis on the independent curriculum. This research uses qualitative research methodology, specifically using phenomenological descriptive techniques. The data collection approach includes the use of a variety of methods, including observation, interviews, and documentation techniques, during the evaluation. The data analysis process requires the application of the Miles and Huberman paradigm. This research involves the use of data analysis techniques to examine the summarized data. The data validation process involves the use of triangulation techniques to ensure accuracy and reliability. Implementation of learning outcomes evaluation includes three main elements: planning, implementation, and identification of factors that facilitate or hinder the implementation of the evaluation. The findings of this research indicate that the process of planning and evaluating learning outcomes requires identifying evaluation objectives, implementing evaluation activities based on these objectives, and considering supporting factors such as student readiness in participating in the learning process. One of the problems that hinders progress is the lack of use of the teaching tools that educators have.